2016
DOI: 10.1073/pnas.1605336113
|View full text |Cite
|
Sign up to set email alerts
|

Ataluren stimulates ribosomal selection of near-cognate tRNAs to promote nonsense suppression

Abstract: A premature termination codon (PTC) in the ORF of an mRNA generally leads to production of a truncated polypeptide, accelerated degradation of the mRNA, and depression of overall mRNA expression. Accordingly, nonsense mutations cause some of the most severe forms of inherited disorders. The small-molecule drug ataluren promotes therapeutic nonsense suppression and has been thought to mediate the insertion of near-cognate tRNAs at PTCs. However, direct evidence for this activity has been lacking. Here, we expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
218
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(242 citation statements)
references
References 41 publications
(104 reference statements)
12
218
4
1
Order By: Relevance
“…The application of PTC readthrough as a therapeutic approach is premised on the inserted amino acid not negatively impacting protein function. The nature of the amino acid introduced at PTCs during readthrough stimulated by the aminoglycoside G418 was recently studied in human HEK293 cells using a proteomic approach (16). Readthrough introduced Arg, Trp, and Cys in a 3/1/1 ratio at a UGA PTC, whereas Gln and Tyr were incorporated in a 8.5/1.5 ratio at UAG, and Gln and Tyr were inserted in equal proportions at UAA (16).…”
Section: Discussionmentioning
confidence: 99%
“…The application of PTC readthrough as a therapeutic approach is premised on the inserted amino acid not negatively impacting protein function. The nature of the amino acid introduced at PTCs during readthrough stimulated by the aminoglycoside G418 was recently studied in human HEK293 cells using a proteomic approach (16). Readthrough introduced Arg, Trp, and Cys in a 3/1/1 ratio at a UGA PTC, whereas Gln and Tyr were incorporated in a 8.5/1.5 ratio at UAG, and Gln and Tyr were inserted in equal proportions at UAA (16).…”
Section: Discussionmentioning
confidence: 99%
“…1). This conclusion is supported by results in Roy et al (11) where they showed that the aminoglycoside, Tobramycin, which binds to the ribosomal A site (15), engendered a dose-dependent reduction of ataluren's readthrough activity. Further research investigating the physical interaction between ataluren and the ribosome, including 3D structural studies, will be important for the development of more potent ataluren derivatives in the future.…”
supporting
confidence: 56%
“…Previous studies reported that ataluren's nonsense suppression activity might be attributable to stabilization of the luciferase enzyme used as a reporter (13,14). The confirmation of ataluren's readthrough activity in numerous nonluciferase systems (including those in Roy et al) (11) and the demonstration that the hypothetical inhibitory molecule, PTC124-AMP, is rapidly converted to ataluren under conditions of in vitro translation, effectively alleviate this concern.…”
mentioning
confidence: 97%
See 2 more Smart Citations